Impacts and compensatory measures: transport infrastructure project from BR-429/RO to the Tupari community of TI Rio Branco, Brazilian Amazon - Bonifácio, Diego Rodrigues; Laroque, Luís Fernando da Silva (Interações (Campo Grande), 2022)
Transport infrastructure projects that impact Indigenous Lands (TI) are subject to the environmental compensation process because the damage caused must be compensated due to the impacts generated in the locality. The work aimed to analyze the politics of indigenous peoples and the interfaces between the Tupari people of the Rio Branco Indigenous Land in Rondônia and the transport infrastructure project BR-429/RO, reflecting on the socio-environmental relations of engineering works on land indigenous peoples. Among the methodological procedures, the documentary survey stands out, having as objects of studies the Environmental Control Plan of BR-429/RO (PCA), the Study of Indigenous Component (ECI), and the Basic Environmental Indigenous Plan (PBAI). It is noted that the indigenous peoples’ policy provides for an environmental compensation process with the potential to mitigate the impacts generated by highways. However, it is necessary to implement measures that seek ecological equivalence in the impacted areas. It is evident that the environmental compensation instrument of the BR-429/RO transport infrastructure project has not been able to be carried out efficiently and also does not meet the real impacts generated on the environment.